An examination of the factors affecting intestinal wall integrity in newborns at birth. (1st February 2018) - Bagci, Soyhan; Mensinga, Daniel; Katzer, David; Merz, Waltraut M.; Reutter, Heiko; Müller, Andreas
Abstract: Background: An understanding of the factors that influence intestinal wall integrity during the transition from fetal to neonatal life is important to elucidate and minimize potential contributions to the development of intestinal pathologies in vulnerable newborns. Objective: To assess the factors affecting intestinal wall integrity of late preterm and term newborns at birth. Methods: The concentrations of serum intestinal fatty acid-binding protein (I-FABP) as biomarker of intestinal wall injury, superoxide dismutase (SOD), and glutathione peroxidase ( Gpx) as parameters of oxidative stress, and blood gas analyses were measured in the arterial cord blood of 80 newborns, delivered by spontaneous vaginal delivery (labor group) or elective cesarean delivery (non-labor group). Results: Compared with the non-labor group, I-FABP, SOD, and Gpx levels were significantly higher in the labor group. I-FABP concentration was inversely correlated with pH and BE and positively correlated with SOD and Gpx concentrations, second stage of labor duration, and active pushing time. Conclusions: This study demonstrates that oxidative stress at birth and prolonged second stage of labor may lead to the intestinal injury, which is reflected in increased serum concentration of I-FABP.